The current challenges affecting the quality of care of HIV/AIDS in the Middle East: Perspectives from local experts and future directions - Ahmed Hakawi; Jacques Mokhbat (Elsevier, 2022)
Objective: This report aimed to reflect the experts' views regarding the challenges affecting the quality of care for people living with HIV in the Middle East. Besides, we integrated experts' opinions and recommendations to offer future directions to improve the quality of care and the overall landscape of HIV in the Middle East. Methods: This review article is based on a comprehensive literature search and the outcomes of several regional meetings that discussed the challenges faced by patients living with HIV in the Middle East. Results: The experts called for actions by various stakeholders to improve the quality of HIV care and implement culturally acceptable programs to face the ongoing stigma and discrimination. Various strategies should also be implemented to improve the HIV awareness among the general population and medical staff, prompt early diagnosis and initiation of ART,and optimize patients' adherence to treatment. Besides, reliable databases, both on national and regional scales, should be implemented to provide reliable data regarding the HIV status in the region. Conclusion: All efforts should be directed towards achieving the UNAIDS the ''90-90-90'' targets, with an acceptable quality of life and minimal complications.